« Les oeuvres d’art parlent d’elles-mêmes » : l’autodescription conceptuelle et son devenir récent - Loubier, Patrice (RACAR : Revue d'art canadienne / Canadian Art Review, 2012)
This study demonstrates how the long-established problematics of idea reappeared in an original fashion in self-descriptive works of conceptual art, as well as in works of contemporary artists quoting their predecessors of the 1960s. A recent drawing by the Quebecois artist Mathieu Beauséjour reveals the complexity of the issues addressed in self-descriptive works. It posts the phrase Les oeuvres parlent d’elles-mêmes, which lends itself to a two-fold reading: either the works speak of or about themselves (self-referentiality of Kosuth’s neon piece Five Words in Blue Neon), or they speak by or for themselves (the tendency toward autonomy of works seeking to rival art history in the usage of the verbal language used to describe them). These two tendencies are examined in three canonical conceptual works: Joseph Kosuth’s Five Words in Blue Neon, Dan Graham’s Schema, and Robert Morris’s Card File. However, several recent productions employ once again the process of self-description, while subverting the transparency and autonomy striven for by the models they take as sources, as is the case in the neons and textual works of the Canadian artists Ron Terada and Kelly Mark, the British artist Tracey Emin, and the Mexican artist Stephan Brüggemann. Through ironic self-depreciation and caustic praise of their forerunners, these works reveal simultaneously the hold of expectations and of institutional conditions, and the ambiguity of their critical position with respect to that context.